Efficacy and Safety of Recanalization Therapy for Acute Ischemic Stroke With Large Vessel Occlusion: A Systematic Review. Issue 7 (July 2020) - Hui, Wen; Wu, Chuanjie; Zhao, Wenbo; Sun, Huan; Hao, Jun; Liang, Hongyan; Wang, Xian; Li, Ming; Jadhav, Ashutosh P.; Han, Youli; Ji, Xunming
Abstract : Background and Purpose: The optimal recanalization strategy for acute ischemic stroke with large vessel occlusion continues to be an area of active interest. Network meta-analysis can provide insight when direct comparative evidence is lacking. Methods: A systematic review of the literature using PubMed, Embase, the Cochrane Central Register of Controlled Trials, and SinoMed was performed, and a search was conducted for clinical trials on ClinicalTrials.gov, the World Health Organization International Clinical Trials Registry Platform, and StrokeCenter.org. Four independent reviewers conducted the study selection, data abstraction, and quality assessments. Results: The literature review identified 17 trials including 3236 patients and 8 ongoing clinical trials. Sample sizes ranged from 7 to 656 participants. Intravenous thrombolysis (IVT) was the most common intervention, followed by IVT plus mechanical thrombectomy (MT), IVT plus intraarterial thrombolysis, intraarterial thrombolysis alone, and MT alone. In the pooled network meta-analysis, IVT+MT was associated with a higher rate of independent functioning. In contrast, IVT was ranked as the most ineffective treatment strategy with respect to neurological functions, while direct MT was ranked as the least safe intervention with respect to all-cause mortality. Also, irrespective of assessment tools, endovascular treatment plus IVT led to higher successful recanalization rate than thrombolysis alone. Conclusions: Compared with other recanalization treatments, IVT+MT seems to be the most effective strategy, without increasing detrimental effects, for thrombolysis-eligible patients with large vessel occlusion-acute ischemic stroke. To improve the current evidentiary basis for recanalization treatment, future trials and real-world studies are warranted and should use unified definitions of symptomatic intracranial hemorrhage and recanalization. Abstract : Supplemental Digital Content is available in the text.